Molecular Electronics: Scanning Tunneling Microscopy and Spectroscopy of Novel Silver–Containing DNA Molecules (Adv. Mater. 35/2019). Issue 35 (26th August 2019) - Fardian‐Melamed, Natalie; Eidelshtein, Gennady; Rotem, Dvir; Kotlyar, Alexander; Porath, Danny
Abstract : Silver‐containing poly(dG)‐poly(dC) DNA holds much promise for molecular nanoelectronics due to its selective metallization, its thin and uniform structure, and its resistance to deformation. In article 1902816, using scanning tunneling microscopy and spectroscopy, Alexander Kotlyar, Danny Porath, and co‐workers reveal a hybrid metal–molecule structure, with silver embedded within the DNA, and an energy gap lower than its DNA‐based peers.